2021
DOI: 10.3390/ijms22063242
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HPV Integrations in Mexican Pre-Tumoral Cervical Lesions Reveal Centromere-Enriched Breakpoints and Abundant Unspecific HPV Regions

Abstract: Human papillomavirus (HPV) DNA integration is a crucial event in cervical carcinogenesis. However, scarce studies have focused on studying HPV integration (HPVint) in early-stage cervical lesions. Using HPV capture followed by sequencing, we investigated HPVint in pre-tumor cervical lesions. Employing a novel pipeline, we analyzed reads containing direct evidence of the integration breakpoint. We observed multiple HPV infections in most of the samples (92%) with a median integration rate of 0.06% relative to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The genomic distribution of individual integration sites is displayed in Figure 2 . A gross preference for peri-centromeric integrations were noted (see Figure 2 ) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genomic distribution of individual integration sites is displayed in Figure 2 . A gross preference for peri-centromeric integrations were noted (see Figure 2 ) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…HPV integration events transpire across all human chromosomes; however, a Chinese study unveiled an excessive concentration of these events on chromosome 19 206 . Although HPV integration might seem stochastic, recent studies have pinpointed a growing array of HPV integration hotspot genes, including FHIT, LRP1B, PP1R37, HECW2, EMBP1, ANKRD50, SPTBN4, LINC00895, LYRM4‐AS1, LINC00374, RBFOX1, CSMD1, CDH13, KLHL4, KLF12, KLF5, CCDC106 207–210 . These genes may hold potential as targets for carcinogenesis and intervention.…”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
“…Based on this observation, actin based peptidomimetics that act as effective substrate competitive inhibitors of human SETD3 were developed [50]. These are 16-residue-long analogs of the actin peptide (66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81), in which the H73 residue is substituted by a simple natural or non-natural amino acid. Among an array of tested peptide analogs, selenomethioninecontaining actin peptide was identified as the most potent inhibitor of the human enzyme, with an IC 50 value of 0.16 µM.…”
Section: Inhibitorsmentioning
confidence: 99%
“…An in vivo study indicated that SETD3 deficient (Setd3 −/− ) mice were viable and showed no symptoms of viral infection [63]. In the context of viral infections, the region encoding the SETD3 protein was recently shown to be an integration site in the precancerous human papillomavirus infections [79]. While only two reports are currently available regarding the importance of the SETD3 protein in viral contagiousness, it is extremely important, taking into account the current pandemic status, to investigate the role of host proteins in the progression of viral infections.…”
Section: Other Diseasesmentioning
confidence: 99%